The acquisition of non-standard features of Croatian in multilingual non-native speakers: a case study - Županović Filipin, Nada (Array, 2014)
In contemporary linguistics the term second language acquisition usually implies the acquisition of the standard variety of a non-mother tongue. That kind of second language acquisition has been thoroughly examined and well defined in literature. On the other hand, incidental and non-institutional second language learning have been described to a much lesser extent, especially for Croatian. The aim of this study is to stress the often neglected fact that in real life situations second language acquisition most frequently takes place in the domain of non-standard varieties. Since scientific studies are often dedicated to the analysis of second language acquisition in terms of an institutionalized process implemented through stages planned and described by the curriculum, our research aims to describe the cases of second language acquisition in natural surroundings, through non-institutional learning. This kind of language acquisition necessarily implies the learning and usage of non-standard varieties. The incidental language learning through which speakers gain knowledge about non-standard features of a second language will be observed through a case study of two non-native speakers of Croatian. The two speakers are an American and an Italian who have been living and working in Zagreb for ten years. First we examined their language learning biographies in order to obtain a clear picture of all the elements that could have influenced their formal (i.e. institutionalized) and informal acquisition of Croatian. We then conducted a semi-structuralized language biographical interview with both of them and carried out a linguistic analysis of the data thus obtained. We focused primarily on lexical analysis because, from the point of view of a non-native speaker, this level harbours the most obvious differences between Standard Croatian and its non-standard varieties. However, we also examined all other linguistic levels that display such differences. Finally, we asked our interviewees to fill in a questionnaire designed to examine their knowledge of non-standard lexical items and the nature of their usage. The items belonged to an inventory of non-standard lexemes found in the most recent Croatian vernacular dictionary (Rječnik hrvatskoga žargona, Sabljak, 2013). The lexemes were selected on the basis of their frequency and popularity and the majority of them were also confirmed in contemporary dictionaries of Standard Croatian (Šonje et al., 2000 and Anić, 2006). The results indicate that the examined speakers show a significant level of familiarity with non-standard language elements, but also point to the speakers’ insecurity when it comes to determining their meaning. Our study shows that the non-standard variety used in learners’ surroundings is an extremely important element of language acquisition when learners live and work in the country whose language they are trying to learn. It also confirms that language acquisition is a complex process influenced by many diverse linguistic and extralinguistic components. We can conclude that further research of this kind is necessary to complete our knowledge on second language acquisition, especially in the subfield which investigates the acquisition of Croatian by non-native speakers.